Социальный и индивидуальный способы материально-производственной жизнедеятельности людей - Суименко, Е. (Социология: теория, методы, маркетинг, 2006)
The author of the article raises and solves the question about social statuses and roles as well as connected with them psychic qualities of human beings needed for individual (“individuative”) and social (“sociative”) ways of material and productive life activity. Recently only the economists have been studying these ways of human activity in the aspects of individual and group (cooperative) work activity. In the author’s opinion, such an approach based on requirements of the economics as a science is inadequate while human element rising in significance in the process of production, labor is being humanized and transformed to a terminal value. From the sociological point of view the author thoroughly analyzes genetic roots of material and productive life activity ways, their advantages and drawbacks, dialectic interrelation as well as cyclic character of the material production development.